Aphasianomics: estimating the economic burden of poststroke aphasia in the United States. Issue 1 (2nd January 2023) - Jacobs, Molly; Ellis, Charles
ABSTRACT: This study was designed to estimate the economic burden of poststroke aphasia in the United States. The economic burden of aphasia was calculated based on three cost factors: medical and healthcare-related expenses, foregone wages from lost labor market activity, and the market value of informal care given within the home. Data from the 2018 National Health Interview Survey (NHIS) were utilized and a pool of stroke survivors with and without poststroke aphasia were identified for the analysis. Stroke survivors in the NHIS sample were matched using 2:1 propensity score matching with poststroke respondents in the 2014 Health and Retirement Survey based on demographic, household, and medical/healthcare characteristics. HRS data were used to calculate medical expenses/healthcare costs, lost wages, and the cost of informal care for each stroke survivor. To determine the cost of poststroke aphasia, respondents with aphasia were matched with those without aphasia and the calculated cost differential was attributed to be from aphasia. The average cost of medical/healthcare expenditures, lost wages, and informal caregiving for individuals with poststroke aphasia was estimated to be 30, 599.78. Individuals with similar demographic characteristics, health status, age, and chronic comorbidities but without aphasia averaged only 24, 276.33. The differential cost between PWA and those without aphasia was 6, 323.45 – the estimated annual economic burden of aphasia. Given that 2.5 million people in the United States suffer from aphasia, these estimates extrapolated to the general population of individuals with aphasia would correspond to 15.8 billion annually. In recent years, a variety of studies and figures relating the cost of illness have been generated across a variety of conditions. This study marks the first attempts to estimate the economic burden of aphasia and follows the framework recommended by the CDC's Economic Impact Analysis. While changes in public health and social support policies have begun to recognize the economic burden of informal caregiving, they often fail to consider the magnitude of lost workforce productivity. Our estimates reinforce the high economic burden of stroke in the United States, acknowledging three categories of related costs. While these estimates provide up-to-date information for policy development and decision-making, additional research is needed into the costs of aphasia and the economic benefits of treatment.